2009
DOI: 10.1111/j.1439-0272.1982.tb02299.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Male Antifertility Agent - Gossypol Acetic Acid. V. Effect of Gossypol Acetic Acid on the Fertility of Male Rats

Abstract: Zusammenfassung Studie über den männlichen Antifertilitätswirkstoff Gossypolazetat V. Effekt von Gossypolazetat auf die Fertilität männlicher Ratten Gossypolazetat wurde männlichen Ratten in einer Dosierung von 7,5 mg/Tier/Tag an sechs Wochentagen über 10 Wochen verabreicht. Nach neun Behandlungswochen konnte keine Implantation bei denjenigen weiblichen Tieren festgestellt werden, die sich mit behandelten männlichen Tieren gepaart hatten. Nach 1 Owöchiger Behandlung mit Gossypol waren sämtliche Spermatozoen im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
2
5
0
Order By: Relevance
“…Thus GAA evidently did not disturb the hypothalamic-pituitarygonadal communication. Our observation is in agreement with that of other groups, who found normal hormone concentrations and reproductive organ weights after gossypol treatment in rats (Wang et al -1979;National Coordinating group -1978;Kalla et al -1982;Chang et al -1980;Xue -1981 ;Hoffer -1980;Bardin et al -1980). Unaltered hormonal G. F. Weinbauer et al status after gossypol treatment has been reported also for monkeys Shandilya et al -1981) and human (Frick et al -1980;Liu et al -1981).…”
Section: Discussionsupporting
confidence: 93%
“…Thus GAA evidently did not disturb the hypothalamic-pituitarygonadal communication. Our observation is in agreement with that of other groups, who found normal hormone concentrations and reproductive organ weights after gossypol treatment in rats (Wang et al -1979;National Coordinating group -1978;Kalla et al -1982;Chang et al -1980;Xue -1981 ;Hoffer -1980;Bardin et al -1980). Unaltered hormonal G. F. Weinbauer et al status after gossypol treatment has been reported also for monkeys Shandilya et al -1981) and human (Frick et al -1980;Liu et al -1981).…”
Section: Discussionsupporting
confidence: 93%
“…Frick and his associates have also not observed any changes in the citric acid and fructose levels in the semen of human volunteers exposed to gossypol, 20 mg/day, for 12 weeks (Frick et al -1981). Our observations that gossypol does not interfere in the androgen synthesis are further supported by the fact that plasma levels of testosterone and LH remain normal after gossypol treatment (National Coordinating Group -1978;Wang et al -1979 a, b;Frick et al -1981;Coutinho et al -1981;Kalla et al -1982).…”
Section: Discussionsupporting
confidence: 70%
“…Different species and varieties of cotton plants differ in concentration of gossypol present in their seeds (Pandey and Thejappa 1975). Several investigators have reported antifertility effects of gossypol in males and females of non-ruminant species (Kalla et al 1982;Bender et al 1988;Randel et al 1992;Olabiyi et al 2006;Meenu 2007, 2008a). The biological effects of gossypol in non-ruminants are cumulative (Berardi and Goldblat 1969).…”
Section: Introductionmentioning
confidence: 99%